Analysis of Social Networks in Modern Society: Case Study on the Use of Social Media Instagram by Sociology Students - Sumitro, Sumitro; Agung Firmansyah; Risma Ade Aryati; Mila Noviana (Tinta Emas Publisher, 2024)
Social media has become an important part of the daily life of modern society, especially among teenagers. This study aims to analyze social networks in modern society with a case study on the use of Instagram social media among adolescents. The method used in this study is a qualitative descriptive method with a case study approach while the data collection technique is through observation, interviews and documentation. The results of the study show that the use of Instagram by teenagers can affect social networks. Teens tend to choose friends with similar interests and follow accounts that are relevant to their interests. However, the use of Instagram can also expand teens' social networks by allowing them to connect with people from different backgrounds. The results of our research show that Instagram has become a significant platform for sociology students to build and expand social networks. Through features such as following, liking, and commenting on posts, sociology students can connect with fellow students, lecturers, and professionals in the field of sociology. In analyzing the data collected, we found that the use of Instagram by sociology students made it possible to expand the social network widely. Sociology students connect with people who share similar interests and interests in sociology, both on campus and off-campus.